Dimensi Eksistensial dan Humanisme dalam Karya Angkatan Pujangga Baru 1966 - Fotivar, Sahputra Daniel; Azzahra, Nadira; Syarifah, Rini; Azizah, Nurul (Yayasan Tri Edukasi Ilmiah, 2025)
The 1966 New Poet Generation was an important milestone in the development of Indonesian literature, which was born amidst the political, social and cultural upheaval after the events of 1965. This research reveals the existential and humanist dimensions in their works, which are often overlooked in previous studies. Using a qualitative approach, this research analyzes poetry, short stories and essays by writers such as Taufiq Ismail, Iwan Simatupang and Ajip Rosidi. The research results show that the work of the Class of 1966 is not only a medium for social criticism but also a space for individual contemplation of the meaning of existence, collective wounds and national identity.